2013
DOI: 10.1371/journal.pone.0055956
|View full text |Cite
|
Sign up to set email alerts
|

Negatively-Marked MCQ Assessments That Reward Partial Knowledge Do Not Introduce Gender Bias Yet Increase Student Performance and Satisfaction and Reduce Anxiety

Abstract: Multiple-choice question (MCQ) examinations are increasingly used as the assessment method of theoretical knowledge in large class-size modules in many life science degrees. MCQ-tests can be used to objectively measure factual knowledge, ability and high-level learning outcomes, but may also introduce gender bias in performance dependent on topic, instruction, scoring and difficulty. The ‘Single Answer’ (SA) test is often used in which students choose one correct answer, in which they are unable to demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 10 publications
(18 reference statements)
2
36
1
1
Order By: Relevance
“…If students are not fully familiar with the testing procedure, it will be less likely for them to make use of the advantages of elimination testing. Yet, previous studies have shown that despite elimination testing initially being new and more complex to them, students still preferred it to the conventional instructions (e.g., Bond et al., ; Bradbard et al., ; Bush, ; Coombs et al., ; Vanderoost et al., ). Therefore, more acquaintance and practice for students may be necessary when this new testing procedure is being implemented, so that students can get more accustomed to it to demonstrate their partial knowledge when they are in doubt about the single‐best answers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If students are not fully familiar with the testing procedure, it will be less likely for them to make use of the advantages of elimination testing. Yet, previous studies have shown that despite elimination testing initially being new and more complex to them, students still preferred it to the conventional instructions (e.g., Bond et al., ; Bradbard et al., ; Bush, ; Coombs et al., ; Vanderoost et al., ). Therefore, more acquaintance and practice for students may be necessary when this new testing procedure is being implemented, so that students can get more accustomed to it to demonstrate their partial knowledge when they are in doubt about the single‐best answers.…”
Section: Resultsmentioning
confidence: 99%
“…() compared the expected answering patterns under correction for guessing and elimination testing, and showed that risk aversion has a bigger impact for test‐takers with partial knowledge, but elimination testing helps to reduce the effect of risk aversion in comparison to correction for guessing. As females are normally considered to be more risk‐averse, empirical studies (Bond et al., ; Bush, ; Vanderoost et al., ) showed that elimination testing reduced the difference between female and male students in terms of the amount of omission responses and test performance, and therefore is less disadvantageous to risk‐averse test‐takers.…”
Section: The Present Studymentioning
confidence: 99%
“…Thus, corrected score presents the true score irrespective of the conventional exam or an exam with negative marking. The Scores with negative marking are lower as compared to the non-negative marking scheme [18,19].…”
Section: Conventional -T1 Negative Marking -T2mentioning
confidence: 99%
“…Az ér-téke tovább csökkenthető, ha a vizsgarendszer nem enged továbblépni egy válasz nélkül hagyott kérésről. Ez a megoldás esetünkben azért lenne használható, mert a jelenlegi pontozási módszer szerint nincsenek "bün-tetőpontok" beépítve a hibás válaszokhoz, egyébként használata nem javasolt [14].…”
Section: Megbeszélésunclassified